(untitled) (Archives of Criminology, 2025)
Border crime in the north-western region of Bangladesh is severe, as illegal activities such as illegal trade, drug trafficking and unauthorised border crossings occur on a regular basis. This study explores the challenges faced by the Bangladesh Police in investigating border crime and examines the nature and causes of these offences. The research uses a qualitative approach, collecting primary data through in-depth interviews with investigation officers from police stations located in border areas. The data were coded, and later revealed several themes and subthemes. The findings of this study indicate that open borders, a lack of supervision and corruption among agencies are the primary causes. These offences are often committed by powerful individuals who exploit young and economically vulnerable populations to carry out such activities. Investigative challenges include insufficient evidence, excessive caseloads, personnel shortages, limited access to information, inadequate financial support, political pressures, misleading sources, hostile environments and poor communication systems in border areas. The study suggests that increasing resources, depoliticising law enforcement, providing support to secure evidence, enhancing inter-agency collaboration and improving access to information can help reduce these investigative challenges.